The effect of magnesium as activator and inhibitor of anaerobic digestion. (October 2016) - Romero-Güiza, M.S.; Mata-Alvarez, J.; Chimenos, J.M.; Astals, S.
Highlights: Mg has been identified as a key element to further anaerobic digestion utilisation. Modelling to correct inoculum background CH4 production at each Mg concentration. Mg inhibition was modelled by a n-component non-competitive inhibition function. Mg 50% inhibitory concentration was estimated at 2140 mg Mg 2+  L −1 . No stimulation or inhibition occurred between 40 and 400 mg Mg 2+  L −1 . Abstract: Anaerobic digestion stands as a key technology in the emerging green energy economy. Mg 2+ has been identified as an important element to improve digesters methane production; however the inhibition risk that high Mg 2+ concentrations can cause to the AD process must also be considered when dosing Mg reagents and wastes containing Mg 2+ . Despite its importance, Mg 2+ stimulation and inhibition mechanisms as well as threshold values are scarce in the literature. This research paper investigates the impact (stimulation and inhibition) of Mg 2+ on pig manure anaerobic digestion. Mathematical modelling was used to better understand the interaction between substrate, inoculum and magnesium, where Mg 2+ inhibition was modelled by a n-component non-competitive inhibition function. Modelling was done on absolute curves rather than specific methane productions curves (new approach) to account for the lower background methane production of the inoculum as the Mg 2+ concentration increased. Results showed that no stimulation or inhibition occurred between 40 (native concentration) and 400 mg Mg 2+  L −1, while minor and major inhibition were observed at 750 and 1000 mg Mg 2+  L −1, and at 2000 and 4000 mg Mg 2+  L −1, respectively. Mg 2+ half maximal inhibition concentration was estimated at 2140 mg Mg 2+  L −1 with an inhibition order of 2. The latter indicates that Mg 2+ inhibition is a progressive rather than a steep inhibition mechanism.